Property Management Excellence : A Values-Based Approach to Real Estate and Property Investing. - Luna, Anthony A. (Advantage Media Group, 2025)
In Property Management Excellence, Anthony A. Luna shares his journey from growing up in the Harbor Area of Los Angeles to becoming CEO of Coastline Equity in his thirties. More than a guide to managing real estate, this book is a blueprint for building a business rooted in integrity and values-driven management.